Practical language in 3 parts - Daulet, F. N.; Kenzhebaeva А. А.; Dauletova G. О. (Journal of Oriental Studies, 2016)
The authors presented the use of the competence-oriented tasks during teaching Chinese. As the sample used lesson from «Practical language in 3 parts,» developed by the Daulet F.N.